1993
DOI: 10.1111/j.1365-2222.1993.tb02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azelastine on substance P content in bronchoalveolar and nasal lavage fluids of patients with allergic asthma

Abstract: The study was carried out to investigate the effect of azelastine on the Substance P (SP) concentration in bronchoalveolar (BAL) and nasal (NAL) lavage obtained from atopic grass pollen asthmatics and non-atopic healthy subjects. In BAL and NAL fluids there was a significant elevation in the baseline concentration of SP between asthmatics and volunteers. Allergen provocation induced a rise of SP in BAL and NAL in asthmatics, but not in volunteers. Azelastine pre-treatment resulted in a significant reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…These results suggest that in chronic bronchitis, kinin generation may be mainly due to t-Kal. Studying the BALF of asthma patients, CHRISTIANSEN et al [33] found the highest kininogenase activity in small molecules after gel filtration chromatography (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). This kininogenase profile appears similar to the profile we found in patients with chronic bronchitis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results suggest that in chronic bronchitis, kinin generation may be mainly due to t-Kal. Studying the BALF of asthma patients, CHRISTIANSEN et al [33] found the highest kininogenase activity in small molecules after gel filtration chromatography (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). This kininogenase profile appears similar to the profile we found in patients with chronic bronchitis.…”
Section: Discussionsupporting
confidence: 82%
“…One hundred millilitres of 0.9% NaCl solution were instilled in 20 mL fractions and immediately removed [24]. Ethylenediamine tetra-acetic acid (EDTA) was added in a concentration of 0.01 M. BAL samples were centrifuged at 2000×g for 10 min, the pellets were discarded and the supernatants were immediately frozen and stored at -70°C until further use.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
“…This would suggest that an extraction process and characterisation of immunoreactivity are essential when measuring peptides in heterogeneous body fluids and may help to explain the diVerence between our data and previous reports demonstrating SP-like immunoreactivity in BAL fluid. [4][5][6] Our laboratory, in an extensive series of experiments, previously concluded that SP cannot be measured without employing an extraction process. 11 Takeyama et al measured SP immunoreactivity (SP-I) after Sep-pak extraction in BAL fluid (6 × 50 ml) from patients with idiopathic pulmonary fibrosis (IPF) and pulmonary sarcoidosis using an enzyme immunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…2 Great interest has surrounded these sensory neuropeptides in the respiratory tract since in vitro they cause many of the features of asthma such as bronchoconstriction, mucus secretion, and airway oedema. 3 Previous studies have measured levels of SP in lavage fluid [4][5][6] but the other sensory neuropeptides NKA and CGRP have not been examined. The aim of this study was to measure and characterise SP, NKA, and CGRP-like immunoreactivity in bronchoalveolar lavage (BAL) fluid in normal subjects and subjects with mild asthma.…”
mentioning
confidence: 99%
“…25 Other studies have shown that treatment with azelastine HCl also decreased LTB4, LTC4 and LTD4 levels. 26,27 Treatment with azelastine HCl has been demonstrated to cause a significant decrease (P  0.05) in Substance P and kinin levels.…”
Section: -24mentioning
confidence: 99%